2018
DOI: 10.1051/matecconf/201816521011
|View full text |Cite
|
Sign up to set email alerts
|

Failure Assessment Diagram (FAD) analysis of fatigue test results for X65 welded joints

Abstract: Abstract. Offshore pipelines transfer oil and gas from seabed to production facility on the surface. The long pipelines are formed by welding of pipe segments, where these welded joints are a source of stress concentration and defects from which fatigue cracks can grow. This work aims to study the behaviour of deep fatigue cracks. In this current work, finite-element based on a parametric study of four-point bending is used to assess the stress intensity factors (SIFs) of deep surface cracks in X65 specimens, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…A Finite-element based on a parametric study of four-point bending is used to assess the stress intensity factors (SIFs) of deep surface cracks in X65 specimens. The test specimen (cut from a pipe) was modeled as a plate using the extended finite element method (XFEM) to study the deep flaws in the specimens [13]. The four-point bending fatigue test was conducted at various loads (load ratio 0.1) until the coupons could no longer support fatigue cyclic loading.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A Finite-element based on a parametric study of four-point bending is used to assess the stress intensity factors (SIFs) of deep surface cracks in X65 specimens. The test specimen (cut from a pipe) was modeled as a plate using the extended finite element method (XFEM) to study the deep flaws in the specimens [13]. The four-point bending fatigue test was conducted at various loads (load ratio 0.1) until the coupons could no longer support fatigue cyclic loading.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that the current assessment of the tested X65 specimens with large cracks shows local throughthickness yielding is likely to occur before global ligament yielding. This work demonstrates a more accurate approach to assess large flaws by considering the SIFs and limit loads by finite element analysis [13].…”
Section: Literature Reviewmentioning
confidence: 99%